2022
DOI: 10.21203/rs.3.rs-1555945/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Role of hippocampal circKcnk9 in visceral hypersensitivity and anxiety comorbidity of Irritable Bowel Syndrome

Abstract: Irritable bowel syndrome (IBS) is a prevalent functional disease. However, its molecular and pathological mechanisms are poorly understood. In this study, neonatal colorectal distension induced visceral hypersensitivity and anxiety comorbidity. The expression of hippocampal circKcnk9, a novel circRNA we termed, was increased significantly in IBS-like rats. Interesting, CA1 shcircKcnk9 treatment inhibited LTP and alleviated visceral hypersensitivity and anxiety in IBS-like rats while overexpression of CA1 circK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…More recent studies suggested that m 6 A modification could mark long non-coding RNA (lncRNA) for processing. 23,24 Considering circKcnk9 was significantly associated with IBS in our previous study, 17 we speculated that circKcnk9 might contribute to the development of chronic visceral pain through m 6 A modification. fluorescent in situ hybridization results showed that circKcnk9 in IBS-like rats significantly co-localized with more c-fos in hippocampus as compared with the controls, indicating that circKcnk9 in hippocampus could activate neurons (Figure 4(a)).…”
Section: Circkcnk9 Is the Major Substrate Of M 6 A In Ibs Ratsmentioning
confidence: 82%
See 4 more Smart Citations
“…More recent studies suggested that m 6 A modification could mark long non-coding RNA (lncRNA) for processing. 23,24 Considering circKcnk9 was significantly associated with IBS in our previous study, 17 we speculated that circKcnk9 might contribute to the development of chronic visceral pain through m 6 A modification. fluorescent in situ hybridization results showed that circKcnk9 in IBS-like rats significantly co-localized with more c-fos in hippocampus as compared with the controls, indicating that circKcnk9 in hippocampus could activate neurons (Figure 4(a)).…”
Section: Circkcnk9 Is the Major Substrate Of M 6 A In Ibs Ratsmentioning
confidence: 82%
“…40 It has been shown that m 6 A can also modulate the expression of circRNAs like other RNA molecules through regulating their generation, stability, or degradation. 41 Considering that our previous studies 17 have demonstrated that circKcnk9, a novel circRNA, was found to adsorb MiR-124-3p in the cytoplasm to induce visceral hypersensitivity in IBS-like rats, it is important to trace the changes of m 6 A modification associated with circKcnk9 in IBS-like rats. Recently, YTHDC1 and its homologous complex have attracted increasing attention.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations